Chinese High School Students’ Leadership Learning Needs and Strategy Choices - Cui, Wenxia; YAN, WENFAN (Advances in Social Sciences Research Journal, 2022)
A survey of 1800 high school students in Shanghai was conducted to examine the Chinese high school students’ leadership learning needs and strategy choice. The results indicated that most of Chinese high school students have a strong interest in leadership learning. Gender, grade level, and school reputation affect the subjects’ leadership learning needs and strategy choices to different degrees. To enhance youth leadership development, school education should expand student leadership development resources to promote active and efficient leadership learning among high school students. Youth education and other related institutions need to play a greater role in enriching the supply of youth leadership learning education.